Chaotic whale optimization algorithm - Kaur, Gaganpreet; Arora, Sankalap (Journal of computational design and engineering, 2018)
Graphical abstract Graphical Abstract AbstractThe Whale Optimization Algorithm (WOA) is a recently developed meta-heuristic optimization algorithm which is based on the hunting mechanism of humpback whales. Similarly to other meta-heuristic algorithms, the main problem faced by WOA is slow convergence speed. So to enhance the global convergence speed and to get better performance, this paper introduces chaos theory into WOA optimization process. Various chaotic maps are considered in the proposed chaotic WOA (CWOA) methods for tuning the main parameter of WOA which helps in controlling exploration and exploitation. The proposed CWOA methods are benchmarked on twenty well-known test functions. The results prove that the chaotic maps (especially Tent map) are able to improve the performance of WOA. Highlights Chaos has been introduced into WOA to improve its performance.Ten chaotic maps have been investigated to tune the key parameter ‘ p’ of WOA.The proposed CWOA is validated on a set of twenty benchmark functions.The proposed CWOA is validated on a set of twenty benchmark functions.Statistical results suggest that CWOA has better reliability of global optimality.